GESTÃO DE RESÍDUOS SÓLIDOS EM EMBARCAÇÕES SÍSMICAS EM OPERAÇÃO NO BRASIL- ESTUDO DE CASO - Bacellar Neto, Alexandre (2006)
The aim of this work is to set out the procedures laid down by the environmental licensing agency for the activity of marine seismic surveying in Brazil, with regard for the management of solid wastes generated on seismic vessels, while attempting to link them to an available bibliographical basis, pertinent to the issue. In preparation of the work, a research was performed about the domestic and international legal aspects applied to the management of solid wastes on vessels that visit Brazilian ports. Alongside this, there was also an analysis of the results from the pollution control project undertaken by PGS Investigação Petrolífera Ltda. during the work of seismic surveying in Blocks BM-J-4 and BM-J-5, from the standpoint of economic and environmental sustainability. It was noted that besides a conflict of competency among the players involved in the issue of solid wastes produced on seismic ships, there is a differentiated treatment given seismic vessels when compared to other types of ships in Brazilian waters. At the end of the work, measures are proposed seeking to adapt the management of solid wastes on seismic ships to the modern procedures already adopted by the coastal countries of the European Union, to make it economically feasible for these ships to discharge solid wastes at local ports, while encouraging them to maintain a project for the separation of wastes on board and avoidance of polluting the marine environment.